Chemical and biological studies on human oxygenases - Thinnes, C; Dr Cyrille C. Thinnes (2014)
As depicted in Chapter I, 2-oxoglutarate- (2OG) dependent oxygenases are ubiquitous in living systems and display a wide range of cellular functions, spanning metabolism, transcription, and translation. Although functionally diverse, the 2OG oxygenases share a high degree of structural similarities between their catalytic sites. From a medicinal chemistry point of view, the combination of biological diversity and structural similarity presents a rather challenging task for the development of selective small molecules for functional studies in vivo. The non-selective metal chelator 8-hydroxyquinoline (8HQ) was used as a template for the generation of tool compound I for the KDM4 subfamily of histone demethylases via application of the Betti reaction. Structural analogue II was used as the corresponding negative control (Figure A). These compounds were characterised in vitro against a range of 2OG oxygenases and subsequently used for studies in cells. I displays selectivity for KDM4 and increases the level of the H3K9me3 histone mark in cells. It has an effect on the post-translational modification pattern of histone H3, but not other histones, and reduces the viability of lung cancer cells, but not normal lung cells, derived from the same patient. I also stabilises hypoxia-inducable factor HIF in cells via a mechanism which seems to be independent from prolyl hydroxylase inhibition. This work is described in Chapters II and III. The chemical biology research in epigenetics is complemented by qualitative analysis conducted in the social sciences at Said Business School. With a global view on how innovation occurs and may actively be fostered, Chapter IV focuses on the potential of epigenetics in drug discovery and how this process may actively be promoted within the framework of open innovation. Areas of focus include considerations of incremental and disruptive technology; how to claim, demarcate, and control the market; how knowledge brokering occurs; and insights about process, management, organisation, and culture of open innovation. In contrast to the open-skies approach adopted for the development of a tool compound in Chapters II and III, a focused-library approach was taken for the generation of a tool compound for the OGFOD1 ribosomal prolyl hydroxylase. The development of a suitable in vitro activity assay for OGFOD1 in Chapter V enabled the development of lead compound III in Chapter VI. III is selective for OGFOD1 against the structurally closely related prolyl hydroxylase PHD2.